2015
DOI: 10.1089/ars.2014.5889
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of Mitochondrial Thioredoxin Reductase Stabilizes Prolyl Hydroxylase 2 and Inhibits Tumor Growth and Tumor-Derived Angiogenesis

Abstract: This work demonstrates an unexpected regulatory link between mitochondrial Txnrd and the JNK-PHD2-Hif-1α axis, which highlights how the loss of Txnrd2 and the resulting altered mitochondrial redox balance impairs tumor growth as well as tumor-related angiogenesis. Furthermore, it opens a new avenue for a therapeutic approach to hinder tumor growth by the simultaneous targeting of both the mitochondrial thioredoxin and glutathione systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 51 publications
1
24
0
Order By: Relevance
“…TrxR2 catalyzes the NADPH-dependent reduction of Trx2, which in its reduced state protects against elevated levels of ROS within the mitochondria 136 . It has been reported that TrxR2 expression is highly elevated in liver cancer 137 , TrxR1 levels on the other hand, the cytosolic isoform, are upregulated in many different cancers including breast 138 , thyroid 139 , prostate 140 , liver 141 , melanomas 142 and colorectal, where strong overexpression of both TrxR and Trx may correlate with overall tumor aggressiveness 143 , perhaps through the HIF-1 pathway 144 . The elevated level of the enzyme is an adaptation to the increased ROS production resulting from the higher metabolic activity of cancer cells 145 .…”
Section: Trx2/trxr2/prx3mentioning
confidence: 99%
“…TrxR2 catalyzes the NADPH-dependent reduction of Trx2, which in its reduced state protects against elevated levels of ROS within the mitochondria 136 . It has been reported that TrxR2 expression is highly elevated in liver cancer 137 , TrxR1 levels on the other hand, the cytosolic isoform, are upregulated in many different cancers including breast 138 , thyroid 139 , prostate 140 , liver 141 , melanomas 142 and colorectal, where strong overexpression of both TrxR and Trx may correlate with overall tumor aggressiveness 143 , perhaps through the HIF-1 pathway 144 . The elevated level of the enzyme is an adaptation to the increased ROS production resulting from the higher metabolic activity of cancer cells 145 .…”
Section: Trx2/trxr2/prx3mentioning
confidence: 99%
“…This hypothesis seems likely in light of growing evidence supporting the existence of a considerable crosstalk between the Trx/TrxR system and GSH-dependent systems [ 51 53 ]. In particular, strong upregulation of Grx2 has recently been reported in mitochondrial TrxR2 -/- mice embryonic fibroblasts [ 54 ]. As mentioned above, similarly to the Trx system, GSH-dependent systems have been reported to play major roles in developmental processes [ 8 10 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cells must depend on strong antioxidant systems to combat the burdens of oxidative stress generated by elevated levels of reactive oxygen species (ROS) accompanying unrestrained malignant growth and serving as both “Savior and Satan” to cell augmentation (e.g., see [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ] and references therein). Two of the major redox regulatory systems in mammals that support increased tumor growth are the thioredoxin (TXN) and the glutathione (GSH) systems [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. The principal functions of these systems are to maintain redox homeostasis at the level of protein-based and low molecular weight thiols, and both systems are comprised of several selenium-containing enzymes (selenoproteins) whose expression levels are influenced by levels of selenium in the diet.…”
Section: Introductionmentioning
confidence: 99%
“…The principal functions of these systems are to maintain redox homeostasis at the level of protein-based and low molecular weight thiols, and both systems are comprised of several selenium-containing enzymes (selenoproteins) whose expression levels are influenced by levels of selenium in the diet. Cancer cells, however, often become increasingly dependent on these systems as well as on other antioxidants in dealing with excessive oxidative damage [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. In recent years, one of the primary foci regarding the forces driving cancer growth has been the disrupted redox homeostasis that accompanies rapid growth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation